Essential ways of using Role-Play Activities in the Lesson - Abdimuminovna, Mukumova Dilshoda (European Journal of Life Safety and Stability (2660-9630), 2021)
Role- play activities are considered as an essential part of the lesson, because they can enhance pupil`s writing and speaking skills in a parallel way. Also teachers can be helped this situation. There are great deal of essential ways of applying this kinds of activities during the lesson. In this article, some of them are given in a short way.